2021
DOI: 10.3389/fnut.2021.743492
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligosaccharide Ameliorates Metabolic Syndrome Induced by Overnutrition via Altering Intestinal Microbiota

Abstract: Chitosan oligosaccharides (COS) play a prebiotic role in many ways, whereas its function on microbiota is not fully understood. In this study, the effects of COS on metabolic syndrome were initially investigated by testing changes in the physiological indicators after adding COS to the diet of mice with high fat (group H) and low fat (group L). The results showed that COS markedly inhibited the accumulation of body weight and liver fat induced by high-fat diet, as well as restored the elevated concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Previous studies have demonstrated that COS inhibited the increases in body weight of obese mice; however, it did not affect the body weight gain of normal mice [ 29 , 30 , 31 ]. Consistent with these findings, we found that continuous supplementation with 400 mg/kg BW COS for 30 days did not affect the body weight gain of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that COS inhibited the increases in body weight of obese mice; however, it did not affect the body weight gain of normal mice [ 29 , 30 , 31 ]. Consistent with these findings, we found that continuous supplementation with 400 mg/kg BW COS for 30 days did not affect the body weight gain of mice.…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that the diet containing 5% COS ( w / w ) markedly inhibited the accumulation of body weight and liver fat induced by HFD and restored the elevated concentration of blood glucose and fasting insulin to normal levels. Next, the analysis of the gut microbiota exhibited that COS specifically enriched Clostridium paraputrificum , Clostridium ramosum , and Akkermansia muciniphila while reducing the abundance of Clostridium cocleatum [ 106 ]. Moreover, Wang et al analyzed the antidiabetic effects of COS in mice with type 2 diabetes mellitus (T2DM).…”
Section: The Modulation Of the Gut Microbiota By Chitosan And Cosmentioning
confidence: 99%
“…By interpreting the mechanism behind dietary foods or nutrients, several major types of active components have been identified, such as oligosaccharides, polysaccharides, and polyphenols, which are emerging as potential prebiotics with both health‐promoting benefits and A. muciniphila ‐enriching effects. As displayed in Table 2, oligosaccharides, including xylooligosaccharide (Zhou et al., 2021), chitosan oligosaccharides (He, Wang, et al., 2020; Wang, Liu, et al., 2021), neoagarotetraose (Liu et al., 2020), and resistant starch (Fu et al., 2021), have been demonstrated to mitigate intestinal mucosal barrier impairment and alleviate metabolic abnormalities, potentially through the stimulation of Akkermansia growth. Additionally, fucoidan (Deng et al., 2021; Wang, Ai, et al., 2020), inulin (Bao et al., 2020), resistant dextrin (Hu et al., 2020), and polysaccharides from flaxseed (Yang et al., 2020), pumpkin (Wu et al., 2021), and kelp (Li, Zha, et al., 2021) exerted anti‐obesity, anti‐diabetes, and anti‐hyperlipidemia effects, along with the positive regulation on Akkermansia level.…”
Section: Diets Regulate a Muciniphila In The Gutmentioning
confidence: 99%